2017
DOI: 10.1002/anie.201704322
|View full text |Cite
|
Sign up to set email alerts
|

Facile and Reversible Formation of Iron(III)–Oxo–Cerium(IV) Adducts from Nonheme Oxoiron(IV) Complexes and Cerium(III)

Abstract: CAN or CeIV(NH4)2(NO3)6 is often used in artificial water oxidation and generally considered to be an outer-sphere oxidant. Herein we report the spectroscopic and crystallographic characterization of [(N4Py)FeIII–O–CeIV(OH2)(NO3)4]+ (3), a complex obtained from the reaction of [(N4Py)FeII(NCMe)]2+ with 2 equiv. CAN or [(N4Py)FeIV=O]2+ (2) with CeIII(NO3)3 in MeCN. Surprisingly, the formation of 3 is reversible, the position of the equilibrium being dependent on the MeCN/water ratio of the solvent. These result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
40
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 47 publications
6
40
3
Order By: Relevance
“…Interestingly, when the rRaman spectra of the reaction solutions of 1-Sc 3+ and 1-Al 3+ with CAN were taken, we found that the bands at 790 and 789 cm -1 completely disappeared (SI, Figures S8b and S9b). Instead, we observed the appearance of a band at 675 cm -1 for 16 O-samples and a band at 645 cm -1 for 18 O-samples (SI, Figures S8b and S9b). Since we have shown above that 1-Ce 4+ exhibits an isotope-sensitive band at 675 cm -1 (vide supra), the results of the rRaman experiments demonstrate unambiguously that 1-Ce 4+ was formed in the substitution reactions of 1-Sc 3+ and 1-Al 3+ with CAN (Scheme 1, reaction c).…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…Interestingly, when the rRaman spectra of the reaction solutions of 1-Sc 3+ and 1-Al 3+ with CAN were taken, we found that the bands at 790 and 789 cm -1 completely disappeared (SI, Figures S8b and S9b). Instead, we observed the appearance of a band at 675 cm -1 for 16 O-samples and a band at 645 cm -1 for 18 O-samples (SI, Figures S8b and S9b). Since we have shown above that 1-Ce 4+ exhibits an isotope-sensitive band at 675 cm -1 (vide supra), the results of the rRaman experiments demonstrate unambiguously that 1-Ce 4+ was formed in the substitution reactions of 1-Sc 3+ and 1-Al 3+ with CAN (Scheme 1, reaction c).…”
mentioning
confidence: 87%
“…[15] More recently, Que and co-workers reported the spectroscopic and crystallographic characterization of [(N4Py)Fe III -O-Ce IV (OH2)(NO3)4] + (N4Py = N,N-bis(2-pyridylmethyl)-N-bis(2-pyridyl)methylamine), which was obtained from the reaction of [(N4Py)Fe II ] 2+ with 2 equiv of CAN or [(N4Py)Fe IV =O] 2+ with Ce III (NO3)3. [16] However, besides the structural information of the Fe-O-Ce species in nonheme iron systems, no other metal-oxo species binding Ce 4+ ion have been reported yet. Moreover, to the best of our knowledge, the effect of the Ce 4+ ion on the chemical properties of high-valent metal-oxo species has never been discussed previously.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3 In this direction, 3d/4f in situ [4][5][6] or well characterised coordination clusters have recently emerged as sustainable catalytic platforms with advantages in their ease synthesis, good abundance (in spite of belonging to the so-called rare earths) and low cost. 7 Our group has established the efficacy of a series of tetranuclear [M II 2Ln III 2L4(X)2(solv)2] (M = Ni, Co, Cu, Zn, X = Cl, NO3, Ln = Y, Dy, Gd) for domino-electro cyclization and Lewis acid reactions, [8][9][10][11] whereas other groups have, successfully, used them in redox, [12][13][14] co-polymerization 15 and carbon dioxide fixation reactions. 16,17 The metal-promoted Suzuki-Miyaura coupling includes organoboron derivatives and carbon electrophiles, and represents a valuable procedure for a C-C bond formation (Scheme 1).…”
Section: The Air Stable and High Yielding Tetranuclear Coordination Cmentioning
confidence: 99%
“…The second group of 3d/4f CCs includes paradigms of wellcharacterised pre-catalyst or postulated active species. [24][25][26][27][28][29][30][31][32][33] The advantage of the isolation and use of well-defined species compared to the former set is the possibility to extract mechanistic information by performing controlled experiments and thus shed light in the catalytic nature of the 3d/4f PCCs. Moreover, this approach allows to fine tune the reaction conditions (i.e.…”
Section: Introductionmentioning
confidence: 99%